Improving English Language Speaking Skills Using â€œAbsyakâ€ On-Line Learning Model for Second Semester in Higher Education - Syakur, Abd.; Sugirin, Sugirin; Margana, Margana; Junining, Esti; Sabat, Yulianto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to improve students' speaking skills. The research sample consisted of 30 students (20 female students and 8 male students) all of whom were studying English, the majority of the sample were second semester students, the form of this study was to analyze (1) teaching and learning plans to speak through the task of information gaps that exist in "Absyak" on-line learning media websites, (2) the implementation of teaching speaking through structured tasks and information gaps with "absyak" on-line learning media websites, (3) teaching teaching evaluation systems through the task gap "absyak" information media website-based online learning, (4) improvement of student speaking using the information gap task on "absyak" website-based on-line learning. This is a classroom action research that takes place in 2 cycles. The subjects of the study were the second semester students of Surabaya Pharmacy Academy, Regular Class A consisting of 30 students in the academic year 2019/2020. Data collected by tests, observation notes and documentation. Data were analyzed descriptively qualitatively. The results showed that learning that was designed using the information gap technique with "absyak". Website-based online learning with cycle procedures. Cycle I results are still not optimal, then continue to the second cycle. In cycle II the results are maximum. Student activities increase every cycle II for learning, student activity, performance indicators, learning processes, completeness scores increase, decrease the number of unfinished and success indicators. Based on the results of research 11 which has been conducted 11 with 1 application of information gap techniques and "absyak" on-line learning website in learning Speaking in the second semester students of the Surabaya pharmacy academy that there is a significant increase in speaking skills from the results of learning achievements of cycle I and cycle II. This means that the students' speaking skills from the stages are increasingly increasing and succeeding well.